Association between alanine aminotransferase and all‐cause mortality rate: Findings from a study on Japanese community‐dwelling individuals. Issue 5 (18th April 2022) - Kawamoto, Ryuichi; Kikuchi, Asuka; Akase, Taichi; Ninomiya, Daisuke; Tokumoto, Yoshio; Kumagi, Teru
Abstract: Background: This study examined the relationship between survival prognosis and alanine aminotransferase (ALT), a critical factor contributing to aging‐related health and mortality. The research is based on a follow‐up study with 6‐ and 10‐year intervals. Methods: The participants included 1, 610 males (63 ± 14 years old) and 2, 074 females (65 ± 12 years old) who were part of the Nomura cohort study conducted in 2002 (first cohort) and 2014 (second cohort). The multivariable‐adjusted hazard ratios (HRs) of death between the baseline health checkup and the end of the follow‐up periods were estimated using a Cox proportional hazards model, controlling for potential confounding factors. Results: The follow‐up survey revealed 180 male deaths (11.2% of male participants) and 146 female deaths (7.0% of female participants). The univariate Cox regression analysis showed a significant increase in the HRs of all‐cause mortality with decreasing ALT levels ( p < 0.001). Furthermore, compared with individuals with ALT levels of 20–29 IU/L, the multivariable‐adjusted HRs (95% confidence interval) for all‐cause mortality were 2.73 (1.59–4.70) for those with ALT levels <10 IU/L, 1.45 (1.05–2.00) for those with ALT levels of 10–19 IU/L, and 1.63 (1.05–2.53) for those with ALT levels ≥30 IU/L. Conclusions: Our findings show that abnormally low ALT levels and high within the normal range were related to all‐cause mortality in Japan's community‐dwelling individuals. Especially, ALT activity may be an important biomarker for predicting the long‐term survival of older adults. Abstract : Analysis of associations between alanine aminotransferase groups and all‐cause mortality during the follow‐up period using survival function. The p ‐values were obtained through a log‐rank test of equality across various strata.